Pop the genius of Andy Warhol - Scherman, Tony 1950-; Dalton, David 1945- (Harper, 2009)
With a sleight of hand, Andy Warhol redefined the boundaries of painting, sculpture, and film, bending them to serve the purpose of his vision. A product of the teeming, exciting, vulgar new world of sixties America, Warhol would take from pop culture as much as pop culture would take from him. Based on extensive new interviews and insight from those who knew him best, Scherman's "Pop" reveals the man behind the public pose.
Includes bibliographical references and index
Keywords: Warhol, Andy -- 1928-1987; Artists -- United States -- Biography; Pop art -- United States; USA; Biografie